Implementasi Keperawatan Pemberian Inhalasi Aromaterapi Lemon Pada Keluarga Penderita Hipertensi Dengan Gangguan Rasa Nyaman - Erman, Imelda; Febriani, Indra; Mahulae, Lidya Margareta; Athiutama, Ari (JKM : Jurnal Keperawatan Merdeka, 2023)
Background: Hypertension is one of the non-communicable diseases (PTM) which is currently increasing in prevalence and incidence and is known as the silent killer disease. The perceived problem is pain and can be reduced through the implementation of aromatherapy. The purpose of this study was to reduce painin hypertensive patients. Methods: The design of this research is descriptive in the form of a case study. The subjects studied were 2 people with the same nursing cases and problems, namely hypertensive patients with impaired sense of comfort in the Work Area of the Merdeka Health Center Palembang. This research was conducted from March 7, 2022 to March 10, 2022. Results: After implementing nursing, it was found that lemon aromatherapy helped reduce hypertension pain with a pain reduction response in patient 1 from a scale of 5 to 3 and patient 2 from a scale of 5 to 3. Conclusion: It is hoped that the implementation of aromatherapy nursing inhypertensive patients with comfort disorders can be developed and can be further developed and become a lesson for further research.